Direct Synthesis of Chromium Perovskite Oxyhydride with a High Magnetic‐Transition Temperature1. (12th August 2014) - Tassel, Cédric; Goto, Yoshihiro; Kuno, Yoshinori; Hester, James; Green, Mark; Kobayashi, Yoji; Kageyama, Hiroshi
Abstract We report a novel oxyhydride SrCrO2H directly synthesized by a high‐pressure high‐temperature method. Powder neutron and synchrotron X‐ray diffraction revealed that this compound adopts the ideal cubic perovskite structure <alternatives> <![CDATA[( Pm3m )]]> <inline-graphic xlink:href="ark:/27927/pgh1c9nv027" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> with O2−/H− disorder. Surprisingly, despite the non‐bonding nature between Cr 3d t2g orbitals and the H 1s orbital, it exhibits G‐type spin ordering at TN≈380 K, which is higher than that of RCrO3 (R=rare earth) and any chromium oxides. The enhanced TN in SrCrO2H with four Cr‐O‐Cr bonds in comparison with RCr3+O3 with six Cr‐O‐Cr bonds is reasonably explained by the tolerance factor. The present result offers an effective strategy to tune octahedral tilting in perovskites and to improve physical and chemical properties through mixed anion chemistry.